Ghostbusters. Frozen empire [videorecording (Blu-Ray + DVD)] - Kenan, Gil; Reitman, Jason, 1977-; Rudd, Paul; Wolfhard, Finn, 2002-; Grace, Mckenna, 2006-; Coon, Carrie, 1981-; Potts, Annie; O'Connor, Celeste, 1998-; Nanjiani, Kumail; Murray, Bill, 1950 September 21-; Oswalt, Patton, 1969-; Hudson, Ernie; et al. (Sony Pictures Home Entertainment, 2024)
The Spengler family returns to where it all started, the iconic New York City firehouse, to team up with the original Ghostbusters gang, who have developed a top-secret research lab to take busting ghosts to the next level. But when the discovery of an ancient relic unleashes an evil force, Ghostbusters new and old must join forces to protect their home and save the world from a second Ice Age.